Projeto e desenvolvimento de uma unidade retificadora utilizando autotransformador de 18 pulsos com conexão delta diferencial generalizada e conversores Boost cascateados para aplicações em HVDC no contexto MEA - More Electric Aircrafts - Soares, Ana Lúcia (2024)
This thesis presents the design and analysis of a rectifier unit formed by a delta-differential symmetrical 18-pulse autotransformer and cascade Boost converters for applications in More Electric Aircraft (MEA), which is denominated as ATRU18PDDS+Boost. The cascaded Boost converters provide DC-link regulation and eliminate the need for interphase transformers (IPTs), interphase reactors (IPRs) or zero-sequence blocking transformers (ZSBTs), decreasing system complexity and increasing reliability. This ATRU18PDDS+Boost operates with an active current shaping strategy in order to meet the harmonic content restrictions imposed by the DO-160F standard and has a low kVA (kilo Volt-Ampere) rating of 21.03%. ATRU18PDDS+Boost was implemented in a system whose power supply is 115VAC and variable frequency from 360Hz to 800Hz, converted into a 540VDC HVDC (High Voltage Direct Current) bus. Computational and experimental results of a 1,2kw prototype are presented, ratifying the theory put forward herein, especially with regard to meeting the limits imposed by the DO-160F standard.